The outcome of more than 3 decades of orphan drug development in alpha-1-antitypsin deficiency: a cross sectional analysis of the FDA Orphan Drug Product designation database - Trudzinski, Franziska; Presotto, Maria Ada; Buck, Emanuel; Herth, Felix; Ries, Markus (Research Square, 2022)
Introduction Alpha-1 antitrypsin deficiency (AATD, OMIM #613490) is a rare metabolic disorder affecting lungs and liver. The purpose of this study is to assess the impact of the US orphan drug act on AATD by providing a quantitative clinical-regulatory insight into the status of FDA orp...